Sintesis Nanopartikel PbO-Ag Dengan Menggunakan Metode Sol-Gel - Iwan Syahjoko Saputra; Suryaneta Suryaneta (Universitas Katolik Widya Karya Malang, 2023)
The synthesis of PbO-Ag nanoparticles was carried out using the sol-gel method using bioreduction from fig leaf extract (Ficus Carica L). PbO is a semi-conducting metal, so it is combined with Ag metal to make PbO a conducting metal. The reason Ag is used is because the stability of silver nanoparticles plays a very important role when being characterized and applied to a product. The nanoparticles formed were characterized by PSA, PZC, XRD, FTIR, UV-Vis, DRS and SEM. From the characteristic results, it was obtained that PbO-Ag could be formed using the sol-gel method using fig leaf bioreductor (Ficus Carica L).